Exclusive breastfeeding lowers the odds of childhood diarrhea and other medical conditions: evidence from the 2016 Ethiopian demographic and health survey - Tesfahun Mulatu; Nigus Bililign Yimer; Birhan Alemnew; Melese Linger; Misgan Legesse Liben (BMC, 2021)
Abstract Background Lack of exclusive breastfeeding during the first 6 months of infant life contributes to childhood morbidity and mortality. This study aimed to investigate the association of exclusive breastfeeding and childhood illnesses in Ethiopia. Methods A secondary data analysis was conducted using data from the 2016 Ethiopian Demographic and Health Survey (EDHS). Descriptive and multivariable logistic regression analyses were carried out. Results A total of 1034 mother-infant pairs were included in the analysis. The overall magnitude of exclusive breastfeeding among infants aged under 6 months was 87.6% (95% CI: 84.3-90.3%). Compared to infants who were non-exclusively breastfed, the odds of having an illness with fever in the last 2 weeks among infants who were exclusively breastfed decreased by 66% (AOR: 0.34; 95% CI: 0.16, 0.75). Similarly, exclusively breastfed infants had lower odds of having an illness with a cough (AOR: 0.38; CI: 0.20, 0.72) and having diarrhea (AOR: 0.33; CI: 0.13, 0.83) compared to non-exclusively breastfed infants. Conclusion Exclusive breastfeeding lowers the odds of an illness with fever, illness with cough and diarrhea. The findings of this study implicate the need for promotion of exclusive breastfeeding in the country.